Cluster headache and anxiety: Results of the EUROLIGHT cluster headache project – An Internet-based, cross-sectional study of people with cluster headache. Issue 1 (20th May 2020) - Pohl, Heiko; Gantenbein, Andreas R; Sandor, Peter S; Schoenen, Jean; Andrée, Colette
Objective: The aim of this study is to evaluate how anxiety influences the burden of disease of cluster headache. Methods: Participants completed a modified version of the EUROLIGHT questionnaire. Anxiety was measured with the anxiety subscale of the Hospital Anxiety and Depression scale. An elevated level of anxiety was assumed when eight or more points were scored. Results: The data of 1089 participants were taken for analysis. The score of the anxiety subscale of the Hospital Anxiety and Depression Scale (HADS-A) correlated weakly with the number of attacks in the last 30 days ( r = 0.17). A score of eight and above in the HADS-A was associated with hurting oneself during an attack (odds ratio (OR) = 2.63), worrying about future attacks (OR = 2.95) and reporting of both failed relationships (OR = 2.81) and career problems (OR = 2.65). The odds of feeling understood by family and friends as well as colleagues and employers were lower in anxious persons (OR = 0.35 and 0.40, respectively). Conclusions: Anxiety complicates dealing with cluster headache and strongly aggravates its burden. Instead of finding help in others, anxious persons feel misunderstood and withdraw; relationships fail and difficulties at work arise.